PREMATURE BIRTH, MORPHOLOGY OF PLACENTA - Kayumova G. M; Mukhtorova Yu. M; Khamroev Kh. N (Ta'lim innovatsiyasi va integratsiyasi, 2024)
The purpose of our work was to study the features of the course of pregnancy, childbirth, the morphological condition of the afterbirth of women who gave birth prematurely to children with developmental delays; to develop a method for the prevention of IGR, perinatal complications. Materials and methods of research. From a total of 2962 births, the course of pregnancy, childbirth, and the morphology of the afterbirth of 50 mothers and their children born prematurely with developmental delay (major RPP) was retrospectively studied. Retarded fetal development was determined according to the table of G.M. Dementieva [4], in which the weight-height coefficient of pregnancy was read. There were 131 (4.4%) premature births. FGR was detected in 50 (38.1%) premature newborns. Comparison groups were 297 (10.5 %) of women and their children with developmental delays, born during a premature pregnancy. The main point of comparison was united by the presence of FGR. The main difference between them was that the main difference between births was premature, while the comparison was timely. This set the task of identifying the effect of miscarriage on the development of FGR. Morphological studies of the afterbirth were carried out using generally accepted methods using mercury and chemical reactions. When comparing the obtained data, methods of variation statistics were used [1].